Effects of Synthetic Short Cationic Antimicrobial Peptides on the Catalytic Activity of Myeloperoxidase, Reducing Its Oxidative Capacity - Tatyana V. Vakhrusheva; Alexey V. Sokolov; Grigoriy D. Moroz; Valeria A. Kostevich; Nikolay P. Gorbunov; Igor P. Smirnov; Ekaterina N. Grafskaia; Ivan A. Latsis; Oleg M. Panasenko; Vassili N. Lazarev (MDPI AG, 2022)
Cationic antimicrobial peptides (CAMPs) have gained attention as promising antimicrobial therapeutics causing lower or no bacterial resistance. Considerable achievements have been made in designing new CAMPs that are highly active as antimicrobials. However, there is a lack of research on their interaction with biologically important proteins. This study focused on CAMPs' effects on myeloperoxidase (MPO), an enzyme which is microbicidal and concomitantly damaging to host biomolecules and cells due to its ability to produce reactive oxygen and halogen species (ROS/RHS). Four CAMPs designed by us were employed. MPO catalytic activity was assessed by an absorbance spectra analysis and by measuring enzymatic activity using Amplex Red- and Celestine Blue B-based assays. The peptide Hm-AMP2 accelerated MPO turnover. Pept_1545 and Hm-AMP8 inhibited both the MPO chlorinating and peroxidase activities, with components of different inhibition types. Hm-AMP8 was a stronger inhibitor. Its Ki towards H2O2 and Cl- was 0.3-0.4 μM vs. 11-20 μM for pept_1545. Peptide tyrosine and cysteine residues were involved in the mechanisms of the observed effects. The results propose a possible dual role of CAMPs as both antimicrobial agents and agents that downregulate MPO activation, and suggest CAMPs as prototypes for the development of antioxidant compounds to prevent MPO-mediated ROS/RHS overproduction.